The Difference in the Profile of Working Memory, Auditory Working Memory, and Spatial Working Memory between Drug, Stimulant, and Methadone Abusers and Normal People - Ahmad Alipour; Tahereh Ghorbani; valiallah Farzad (Drug Control Headquarters, Research and Education Office, 2015)
Objective: The present study was an attempt to examine the difference in the profile of working memory, auditory working memory, and spatial working memory between drug, stimulant, and methadone abusers and normal people. Method: This study was a causal-comparative one with between-group comparison methodology. All the individuals addicted to opiates, stimulants, and methadone who had referred to Khomeini treatment centers of the city from September 2013 to February 2014 constituted the statistical population of the study. The number of 154 abusers (54 drug abusers, 50 stimulant abusers, and 50 methadone abusers) and the number of 50 normal participants were chosen as the sample of the study by purposive sampling method. The participants responded to Wechsler Memory Scale—third edition (WMS-III). Results: There was a significant difference between the normal group and drug, stimulant, and methadone abusers in terms of working memory, auditory working memory, and spatial working memory. Conclusion: Drug and stimulant use leads to sustained damage in cognitive processes such as working memory. However, research indicates that these cognitive processes will improve with the passage of time.